Case report: Fatal infantile hypertonic myofibrillar myopathy with compound heterozygous mutations in the CRYAB gene - Zhang, Shan-shan; Gu, Li-niu; Zhang, Teng; Xu, Lu; Wei, Xiang; Chen, Su-hong; Shi, Su-jie; Sun, Da-quan; Zhou, Shao-hong; Zhao, Qian-ye (Frontiers in Pediatrics, 2023)
Background Fatal infantile hypertonic myofibrillar myopathy (FIHMM) is an autosomal recessive hereditary disease characterized by amyotrophy, progressive flexion contracture and ankylosis of the trunk and limb muscles, apnea and respiratory failure, and increased creatine phosphate levels. It is caused by mutations in the CRYAB gene, and only around 18 cases including genetic mutations have been reported worldwide. All patients with FIHMM develop respiratory distress, progressive stiffness of the limbs, and have a poor prognosis. However, no effective treatment for CRYAB-associated respiratory failure has been reported. Here, we report a case of FIHMM with a novel heterozygous missense mutation. Case Presentation A 2-year-old female developed scoliosis of the lumbar spine and restrictive ventilatory dysfunction in infancy. She was admitted to the hospital with labored breathing on the third day after the second injection of inactivated poliomyelitis vaccine. Acute respiratory failure, pneumothorax, and cardiac arrest arose in the patient during hospitalization, and progressive stiffness of the trunk and limb muscles appeared, accompanied by obvious abdominal distension and an increase in phosphocreatine kinase levels. Screenings for genetic metabolic diseases in the blood and urine were normal. Electromyography revealed mild myogenic damage. A muscle biopsy indicated the accumulation of desmin, α-crystallin, and myotilin in the musculus biceps brachii, and dense granules were observed in muscle fibers using electron microscopy. Mutation analysis of CRYAB revealed a novel heterozygous missense mutation in the proband, c.302A > C (p.His101Pro) and c.3G > A (p.Met1Ile), which inherited from her asymptomatic, heterozygous carrier parents, respectively. The proband was finally diagnosed as FIHMM. One month after the FIHMM diagnosis, the child died of respiratory failure. Conclusion We report a case of FIHMM with a novel heterozygous missense mutation of CRYAB. This finding might improve our understanding of FIHMM and highlight a novel mutation in the Chinese population.